'All in it Together'? Ethnoreligious Labour-Market Penalties and the Post-2008 Recession in the UK. (April 2015) - Khattab, Nabil; Johnston, Ron; Manley, David
The existence of ethnic penalties in the operations of the UK labour market is well established, although many studies have focused upon only unemployment and income as measures of labour-market performance. Few have looked at changes in those penalties over time, especially during a period including a major recent recession, and whether they were experienced widely throughout the population—whether people were 'all in it together' according to the government's rhetoric defending its post-2010 austerity programme. This paper evaluates that claim's validity by exploring differences among eighteen separate ethnoreligious groups across a wider range of labour-market performance measures: it assesses not only whether there were ethnic penalties throughout the period but also whether they were exacerbated during the recession that began in 2008. Statistical modelling shows that many were indeed exacerbated—in the percentage employed part-time rather than full-time, the percentage overqualified for their chosen jobs, the percentage of older adults who become economically inactive prematurely, and income levels—but not unemployment levels. Muslim groups, especially those from Asia, suffered the most extensive penalties, and the greatest exacerbation of them during the recession.